2018
DOI: 10.1002/eat.22832
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of co‐occurring food avoidance and alcohol use disorder in an adult: Possible avoidant restrictive food intake disorder?

Abstract: However, excessive alcohol intake had reoccurred at 3-month follow-up, accompanied by increases in negative affect and impairment due to eating, indicating that longer-term therapy may be required for this group of people.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 15 publications
1
11
0
Order By: Relevance
“…Multiple published case reports and case series have described the use of various forms of cognitive-behavioral therapy (CBT) for children [13,17,18] and adults [19,5] with ARFID. Common elements across CBT interventions for ARFID include regular eating [5,13], self-monitoring of food intake [5], exposure and response prevention [13,16], relaxation training [17,16, and behavioral experiments [5]. In one case study, a 16-year-old boy was able to significantly increase his consumption of proteins, fruits, and vegetables, and significantly decrease his eating-related distress after 11 sessions of CBT supplemented with in-home meal interventions in which his mother reinforced the consumption of novel foods [16].…”
Section: Available Data On the Treatment Of Arfidmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple published case reports and case series have described the use of various forms of cognitive-behavioral therapy (CBT) for children [13,17,18] and adults [19,5] with ARFID. Common elements across CBT interventions for ARFID include regular eating [5,13], self-monitoring of food intake [5], exposure and response prevention [13,16], relaxation training [17,16, and behavioral experiments [5]. In one case study, a 16-year-old boy was able to significantly increase his consumption of proteins, fruits, and vegetables, and significantly decrease his eating-related distress after 11 sessions of CBT supplemented with in-home meal interventions in which his mother reinforced the consumption of novel foods [16].…”
Section: Available Data On the Treatment Of Arfidmentioning
confidence: 99%
“…In addition to the heterogeneity of clinical presentation, ARFID is also quite diverse in terms of age, demographics, and comorbidities, highlighting the difficulty in identifying a universally applicable treatment approach. For example, ARFID has been reported in very young children [3 **], adolescents [4 *], and adults [5], and several studies have highlighted that both males and females present with the disorder [6,7]. Other investigations have underscored numerous potential psychiatric and medical comorbidities, including autism spectrum disorder [8] and gastrointestinal disorders [6], which may further individualize treatment needs.…”
Section: Introductionmentioning
confidence: 99%
“…Published research on the treatment of older children and adolescents is limited to retrospective chart reviews (Bryson, Scipioni, Essayli, Mahoney, & Ornstein, 2018; Makhzoumi et al, 2019), case studies (Thomas, Brigham, Sally, Hazen, & Eddy, 2017), and case series (Dumont, Jansen, Kroes, de Haan, & Mulkens, 2019; Rienecke, Drayton, Richmond, & Mammel, 2020). A growing number of reports have highlighted the potential application of cognitive‐behavioral (Görmez, Kılıç, & Kırpınar, 2018; Steen & Wade, 2018; Zucker et al, 2019), family‐based (Eckhardt, Martell, Lowe, Le Grange, & Ehrenreich‐May, 2019; Lock et al, 2019; Rienecke et al, 2020; Spettigue, Norris, Santos, & Obeid, 2018), and parent‐management (Dahlsgaard & Bodie, 2019) approaches. For example, a case series of 11 children and adolescents ages 10–18 years found that cognitive‐behavioral therapy (CBT) delivered in an intensive day‐hospital format resulted in significant reductions in ARFID symptoms (Dumont et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The most common conclusion of authors reviewing the state of RCTs across a variety of disciplines is that we do not need to rely on RCTs as the only authoritative approach to resolving uncertainty about which treatments to recommend (Bothwell et al, ). Qualitative studies (e.g., Becker, Arrindell, Perloe, Fay, & Stiegel‐Moore, ), case reports (e.g., Steen & Wade, ), case series (e.g., Waller et al, ), and meta‐analyses and network meta‐analyses (e.g., Watson et al, ), can all add complementary value to RCTs. Qualitative studies can be used to generate hypotheses about useful new treatment modules.…”
Section: Strategies For Future Researchmentioning
confidence: 99%